Prospek Utama Pengembangan Energi Terbarukan Di Negara-Negara ASEAN - Syaifuddin Yana; Muhammad Nizar; Ardhana Yulisma (Jurnal Serambi Engineering, 2021)
The economic development of a country depends on  sustainable energy sources that meet   basic human needs. Government policy on energy conservation is an effort to maintain the stability of energy security that affects the economic development  of a country. Southeast Asia is experiencing rapid economic growth and development, combined with population growth and urbanization, as well as increased access to basic services. This study aimed to determine the seven key factors  considered that shape energy in Southeast Asia. Based on the panel data model, it showed that energy demand in the ASEAN region greatly influences  GDP per capita; demographics  and urbanization; air quality, climate risk, and environmental degradation; energy accessibility, affordability, and security; investment and financial ; as well as energy policies, prices, and regulations.